2020
DOI: 10.1111/ffe.13292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment at the temperature above β‐transus on the microstructures and fatigue properties of pure Ti

Abstract: Commercially pure Ti (CP-Ti) was heat treated at 1273 K (1000 C), which was higher than β-transus temperature, followed by water quenching. The dwell time at 1000 C was changed from 1 to 240 h. The heat treatment at 1000 C resulted in α grain coarsening, whereas martensitic transformation occurred due to the rapid cooling from β phase. The hardness increased by the martensitic transformation, where higher hardness was achieved by longer dwell time at 1000 C. However, the fatigue strengths of the heat-treated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The present authors have previously reported 27,34,3740) that a relatively coarse microstructure with low strength was the predominant crack initiation site in CP titanium and a Ti6Al4V alloy with a bimodal grain size distribution during fatigue tests. Uematsu et al 41) reported that a fatigue crack was initiated at the untransformed coarse grains in the CP titanium heat-treated at a temperature above the ¢ transus. These studies indicate that the weak region, which is the un-nitrided region with low hardness and low nitrogen content in the present study, acts as a crack initiation site in CP titanium having a heterogeneous microstructure.…”
Section: Fatigue Crack Initiation and Propagation Behaviors In Cp Tit...mentioning
confidence: 99%
“…The present authors have previously reported 27,34,3740) that a relatively coarse microstructure with low strength was the predominant crack initiation site in CP titanium and a Ti6Al4V alloy with a bimodal grain size distribution during fatigue tests. Uematsu et al 41) reported that a fatigue crack was initiated at the untransformed coarse grains in the CP titanium heat-treated at a temperature above the ¢ transus. These studies indicate that the weak region, which is the un-nitrided region with low hardness and low nitrogen content in the present study, acts as a crack initiation site in CP titanium having a heterogeneous microstructure.…”
Section: Fatigue Crack Initiation and Propagation Behaviors In Cp Tit...mentioning
confidence: 99%